- Thread starter
- #1

I am reading Gerard Walschap's book: "Multivariable Calculus and Differential Geometry" and am focused on Chapter 1: Euclidean Space ... ...

I need help with an aspect of the proof of Theorem 1.3.1 ...

The start of Theorem 1.3.1 and its proof read as follows:

I tried to understand how/why

\(\displaystyle \text{det} ( v_1, \cdot \cdot \cdot , v_n ) = \sum_{ \sigma } a_{ \sigma (1) 1 } , \cdot \cdot \cdot , a_{ \sigma (n) n } \ \text{det} ( e_{ \sigma (1) } , \cdot \cdot \cdot , e_{ \sigma (n) } \)

where the sum runs over all maps \(\displaystyle \sigma \ : \ J_n = \{ 1 , \cdot \cdot \cdot , n \} \to J_n = \{ 1 , \cdot \cdot \cdot , n \}\)

... so ...

... I tried an example with \(\displaystyle \text{det} \ : \ (\mathbb{R}^n)^n \to \mathbb{R}\) ... ...

so we have \(\displaystyle v_1 = \sum_k a_{ k1 } e_k = a_{11} e_1 + a_{21} e_2\)

and

\(\displaystyle v_2 = \sum_k a_{ k2 } e_k = a_{12} e_1 + a_{22} e_2 \)

and then we have

\(\displaystyle \text{det} ( v_1, v_2 )\)

\(\displaystyle = \text{det} ( a_{11} e_1 + a_{21} e_2 , a_{12} e_1 + a_{22} e_2 )\)

\(\displaystyle = a_{11} a_{12} \ \text{det} ( e_1, e_1 ) + a_{11} a_{22} \ \text{det} ( e_1, e_2 ) + a_{21} a_{12} \ \text{det} ( e_2, e_1 ) + a_{21} a_{22} \ \text{det} ( e_2, e_2 )\)

\(\displaystyle = \sum_{ \sigma } a_{ \sigma (1) 1 } a_{ \sigma (2) 2 } \ \text{det} ( e_{ \sigma (1) }, e_{ \sigma (2) } ) \)

where the sum runs over all maps

\(\displaystyle \sigma \ : \ J_n = \{ 1, 2 \} \to J_n = \{ 1 , 2 \}\) ...

... ... that is the sum runs over the two permutations

\(\displaystyle \sigma_1 = \begin{bmatrix} 1 & 2 \\ 1 & 2 \end{bmatrix}\) and \(\displaystyle \sigma_2 = \begin{bmatrix} 1 & 2 \\ 2 & 1 \end{bmatrix}\)

BUT how does the formula \(\displaystyle \sum_{ \sigma } a_{ \sigma (1) 1 } a_{ \sigma (2) 2 } \ \text{det} ( e_{ \sigma (1) }, e_{ \sigma (2) } \) ...

... incorporate or deal with the terms involving \(\displaystyle \text{det} ( e_1, e_1 )\) and \(\displaystyle \text{det} ( e_2, e_2 )\) ... ... ?

Hope someone can help ...?

Peter

I need help with an aspect of the proof of Theorem 1.3.1 ...

The start of Theorem 1.3.1 and its proof read as follows:

I tried to understand how/why

\(\displaystyle \text{det} ( v_1, \cdot \cdot \cdot , v_n ) = \sum_{ \sigma } a_{ \sigma (1) 1 } , \cdot \cdot \cdot , a_{ \sigma (n) n } \ \text{det} ( e_{ \sigma (1) } , \cdot \cdot \cdot , e_{ \sigma (n) } \)

where the sum runs over all maps \(\displaystyle \sigma \ : \ J_n = \{ 1 , \cdot \cdot \cdot , n \} \to J_n = \{ 1 , \cdot \cdot \cdot , n \}\)

... so ...

... I tried an example with \(\displaystyle \text{det} \ : \ (\mathbb{R}^n)^n \to \mathbb{R}\) ... ...

so we have \(\displaystyle v_1 = \sum_k a_{ k1 } e_k = a_{11} e_1 + a_{21} e_2\)

and

\(\displaystyle v_2 = \sum_k a_{ k2 } e_k = a_{12} e_1 + a_{22} e_2 \)

and then we have

\(\displaystyle \text{det} ( v_1, v_2 )\)

\(\displaystyle = \text{det} ( a_{11} e_1 + a_{21} e_2 , a_{12} e_1 + a_{22} e_2 )\)

\(\displaystyle = a_{11} a_{12} \ \text{det} ( e_1, e_1 ) + a_{11} a_{22} \ \text{det} ( e_1, e_2 ) + a_{21} a_{12} \ \text{det} ( e_2, e_1 ) + a_{21} a_{22} \ \text{det} ( e_2, e_2 )\)

\(\displaystyle = \sum_{ \sigma } a_{ \sigma (1) 1 } a_{ \sigma (2) 2 } \ \text{det} ( e_{ \sigma (1) }, e_{ \sigma (2) } ) \)

where the sum runs over all maps

\(\displaystyle \sigma \ : \ J_n = \{ 1, 2 \} \to J_n = \{ 1 , 2 \}\) ...

... ... that is the sum runs over the two permutations

\(\displaystyle \sigma_1 = \begin{bmatrix} 1 & 2 \\ 1 & 2 \end{bmatrix}\) and \(\displaystyle \sigma_2 = \begin{bmatrix} 1 & 2 \\ 2 & 1 \end{bmatrix}\)

BUT how does the formula \(\displaystyle \sum_{ \sigma } a_{ \sigma (1) 1 } a_{ \sigma (2) 2 } \ \text{det} ( e_{ \sigma (1) }, e_{ \sigma (2) } \) ...

... incorporate or deal with the terms involving \(\displaystyle \text{det} ( e_1, e_1 )\) and \(\displaystyle \text{det} ( e_2, e_2 )\) ... ... ?

Hope someone can help ...?

Peter

Last edited: